ANALISIS KOMPETENSI, BUDAYA ORGANISASI, DISIPLIN, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA APARATUR DESA - Sudomo; Suyanto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to analyze the factors that influence the performance of village officials, with a focus on competence, organizational culture, discipline, education and training. Village apparatus is important in managing government and public services at the village level. Therefore, it is important to understand the factors that can affect their performance. The research was conducted in Cariu District, Bogor Regency by taking 100 village apparatus employees as research samples. The results of the data analysis show that the competence of village officials has a significant positive relationship with their performance. The higher the competence of village officials, the better their performance in carrying out their duties. In addition, a good organizational culture is also positively related to the performance of village officials. An organizational culture that creates a cooperative, transparent and service-oriented work environment encourages village officials to work more effectively. In addition to competence and organizational culture, discipline also plays an important role in improving the performance of village officials. A high level of discipline makes village officials more able to follow established work procedures and complete tasks on time. Education and training also have a positive impact on the performance of village officials. By increasing their knowledge and skills through education and training, village officials can be better prepared and competent in carrying out their duties. Based on these findings, it is suggested that the village government and related agencies pay greater attention to the competency development of village officials through relevant education and training programs. In addition, it is necessary to build a strong organizational culture that encourages cooperation and good service among village officials. In addition, strict disciplinary enforcement must also be applied to improve the performance of village officials as a whole.